Pembentukan Karakter Siswa dalam Konteks Lingkungan Sekolah dan Keluarga serta Komunitas Perspektif Ekologi Bronfenbrenner - Ranti Oktaviana; Umi Khiftiyah; Fauzia Yuliani; Wahyu Dewi Utari (Bulletin of Indonesian Islamic Studies, 2023)
This study aims to examine the role of the educational environment in shaping students' character using Bronfenbrenner’s ecological systems theory integrated with related theories on moral, social, and psychological development. The findings indicate that the quality of physical school facilities, a school culture that supports moral values, the exemplary role of teachers, and the involvement of family and community synergistically influence students’ character development. Social interactions with peers and the impact of social media also play significant roles that require careful management in character education. A value-based approach grounded in Islamic principles provides a strong ethical foundation within the Indonesian context, reinforcing the internalization of values such as honesty, responsibility, and compassion. Temporal dynamics and social changes also present both challenges and opportunities for adaptive and holistic innovations in character education. These findings confirm that character formation is the result of complex interactions between individuals and multiple interrelated social systems; thus, character education strategies must be designed contextually, collaboratively, and sustainably.